Emerging Biomarkers and Targeted Therapies in Feline Mammary Carcinoma - Andreia Gameiro; Ana Catarina Urbano; Fernando Ferreira (Veterinary Sciences, 2021)
Feline mammary carcinoma (FMC) is a common aggressive malignancy with a low survival rate that lacks viable therapeutic options beyond mastectomy. Recently, increasing efforts have been made to understand the molecular mechanisms underlying FMC development, using the knowledge gained from studies on human breast cancer to discover new diagnostic and prognostic biomarkers, thus reinforcing the utility of the cat as a cancer model. In this article, we review the current knowledge on FMC pathogenesis, biomarkers, and prognosis factors and offer new insights into novel therapeutic options for HER2-positive and triple-negative FMC subtypes.